Neuroendocrine-immune relatioships in rats females - Zajats, Lyubomyr M; Polovynko Іlona S; Zukow, Walery; Yanchiy, Roman I; Mysakovets, Oleksiy G; Mel’nyk, Oksana I; Hrytsak, Yaroslav L (Journal of Education, Health and Sport, 2017)
Background. Previously, in line with the concept of the neuroendocrine-immune complex, we analyzed the relationships between the parameters of the autonomic nervous and endocrine systems, on the one hand, and the parameters of immunity, on the other hand, in male rats. The purpose of this study is to analyze such interactions in female rats. Material and methods. In 60 females of rats, parameters of HRV, blood levels of hormones and electrolytes as well as parameters of leukocytogram, immunocytogram, thymocytogram and splenocytogram were determined. The coefficients of canonical correlation R between neuroendocrine parameters, on the one hand, and parameters of immunity, on the other hand, were calculated. Results. The following values of R for neuroendocrine parameters were found. Sympathetic tone: 0,702; Vagal tone: 0,756; Moda HRV: 0,896; the thickness of the Fascicular zone of adrenal cortex: 0,727; Glomerular zone: 0,650; Reticular zone: 0,442; plasma level of Corticosterone: 0,601; Testosterone: 0,753; Triiodo-thyronine: 0,544; Thyroxine: 0,441; Mineralocorticoid activity: 0,474; Calcitonine activity: 0,580; Parathyrine activity: 0,551. Conclusion. The results obtained by us complement and specify the concept of a triune neuroendocrine-immune complex.